Z-Ligustilide Induces c-Myc-Dependent Apoptosis via Activation of ER-Stress Signaling in Hypoxic Oral Cancer Cells - Hsu, Ren-Jun; Peng, Kui-Yuan; Hsu, Wen-Lin; Chen, Yu-Tang; Liu, Dai-Wei (Frontiers in Oncology, 2022)
Z-ligustilide is extracted from Angelica sinensis (Oliv.) Diels may exert potential benefits on cancer treatment. Previous research has reported that it has anti-cancer activities on several cancer cells. However, study of ligustilide on oral cancer cells has not been reported, especially under hypoxia. This study will focus on the molecular mechanism of ligustilide-induced apoptosis in hypoxic oral cancer cells. We indicated that in hypoxic TW2.6 cells, ligustilide inhibited cell migration and induced caspase-dependent apoptosis. c-Myc accumulation accompanied with the BH3 only members indicated that ligustilide may induce c-Myc-dependent apoptosis. Meanwhile, we reported that ligustilide impacted ER stress signaling. By using inhibitors of c-Myc, IRE1α, and a couple of ER stress inhibitors, we found that cell morphologies or cell viability have been rescued to degrees. In addition, ligustilide can increase the expression of γ-H2AX and enhance the occurrence of DNA damages in oral cancer cells after radiation treatment. This result means that ligustilide can be used as a radiation sensitizer. Altogether, we proposed that ligustilide may induce c-myc-dependent apoptosis via ER stress signaling in hypoxic oral cancer cells.